Comparative analysis of multi-link selection strategies for next-generation aeronautical communications - Subasu, Stefan; Al-Rubaye, Saba; Tsourdos, Antonios; Newton, Paul; Tonnerre, Arnaud (Institute of Electrical and Electronics Engineers (IEEE), 2025)
Next-generation aviation demands seamless connectivity across heterogeneous networks, yet maintaining uninterrupted links under strict performance requirements remains a major challenge. Current Aeronautical Telecommunication Network (ATN) mechanisms depend on static tables that overlook airframe shadowing and dynamic flight conditions, limiting their effectiveness in complex radio environments. This paper delivers a comprehensive evaluation of terrestrial and non-Terrestrial networks (NTN) and benchmarks twelve link-selection algorithms across representative Air-To-Satellite (A2Sat) and Air-To-Ground (A2G) scenarios. The system design introduces an AI-driven dual-layer onboard controller that integrates predictive planning with real-Time adaptation. Simulation results show that this approach enables proactive link switching, enhances stability, and supports efficient flight operations. To sum up, this work can be a roadmap for ATN architectures by delivering resilient, hyper-connected communications required for next-generation aviation and paves the way for this implementation.
Keywords: 40 Engineering; 4001 Aerospace Engineering; 46 Information and computing sciences; Aeronautical communications; multi-link; decision-making; aeronautical telecommunication network.